CT diagnosis of an iatrogenic bile duct injury. (29th September 2014) - Mbarushimana, Simon; Morris-Stiff, Gareth; Hassn, Ahmed
Abstract : Bile duct injuries are a recognised complication of cholecystectomy and a number of options exist for their evaluation. A 44-year-old woman presented with a suspected biliary leak 11 days following an open cholecystectomy. Her medical history was significant for biliopancreatic diversion 2 years previously. An ultrasound scan demonstrated a perihepatic collection but no dilation of the biliary tree was observed. The patient's surgical history and the lack of biliary dilation precluded an endoscopic retrograde cholangiopancreatography or percutaneous transhepatic cholangiography, and she could not undergo an MR cholangiopancreatography due to claustrophobia. A CT cholangiogram was performed and clarified the location of the injury, facilitating operative identification and repair of the bile duct. CT cholangiography performed as a dynamic procedure is useful as a means of identifying bile duct injuries.